The invention of banking - Terpstra, Nicholas; Leesti, Elizabeth; Films for the Humanities (Firm) (Princeton, NJ. : Films for the Humanities & Sciences, 2004)
In 13th- and 14th-century Tuscany, money became the new tool of power as industry, trade, and finance flourished. This program follows the remarkable rise of the great banking families whose groundbreaking innovations in finance led to the economics of international big business practiced today. Merchant bankers also supported the aims of the Catholic Church by using their extraordinary wealth to become patrons for charities and spectacular works of art and architecture
'A presentation of Films for the Humanities & Sciences'
Interviews with Nicholas Terpstra and Dr. Elizabeth Leesti, historians at the University of Toronto, are featured
Keywords: Documentary films; Banks and banking -- History; Merchant banks -- History; Fourteenth century; Tuscany (Italy) -- History